Urine-based testing for Chlamydia trachomatis among young adults in a population-based survey in Croatia : feasibility and prevalence - Božičević, Ivana (Array, 2011)
Background We assessed the feasibility of collecting urine samples for testing on genital Chlamydia trachomatis infection in a population-based survey, and prevalence of this infection among young people aged 18-25 in Croatia. In Croatia, as in the other countries of Eastern Europe, there is a lack of data on prevalence of C trachomatis in the general population, including young adults. Methods We sampled participants using a nationally representative, multi-stage stratified probability sample of young men and women. Detection of C trachomatis DNA in urine samples was performed by using a real-time PCR assay COBAS® TaqMan® CT Test, v2.0. Results Overall, 1005 young adults participated in the behavioural part of the survey, and 27.9% men and 37.5% women who were sexually experienced agreed to provide urine samples for testing on C trachomatis. Using multivariate analysis, women were significantly more likely to provide urine samples than men (aOR = 1.53, 95% CI 1.14-2.06) as were those who reported no condom use at last intercourse (aOR = 1.95, 95% CI 1.44-2.62). Prevalence of C trachomatis infection among those who were sexually experienced was 7.3% in men and 5.3% in women. Conclusions Population-based surveys that use probabilistic sampling are a feasible way to obtain population estimates of C trachomatis prevalence among young adults in Croatia, but it is challenging to obtain an adequate response rate. The prevalence of C trachomatis among young adults in Croatia found in this study was higher than that found in other European countries with similar survey response rates.